Active Learning Through Discussion in E-Learning - Wahyuningsih, Daru (International Journal of Active Learning, 2016)
Active learning is generally made by a lecturer in learning face to face. In the face to face learning, lecturer can implement a variety of teaching methods to make students actively involved in learning. This is different from learning that is actuating in e-learning. The main characteristic of e-learning is learning that can take place anytime and anywhere. Special strategies are needed so that lecturer can make students play an active role in the course of e-learning. Research in order to obtain the result that certain strategies can make an active student in course of e-learning was conducted using quasi-experimental research. This study is imposed on three courses in Study Program of Physics Education (Program Studi Pendidikan Fisika) of Sebelas Maret University (Universitas Sebelas Maret) that are the Geophysics, Learning Technology, and Measurement courses. In all three subjects, the researchers apply a strategy and then analyzed the results through statistical data of each course of e-learning. Based on the research, it is showed that students can conduct active learning by means of discussions in e-learning.How to CiteWahyuningsih, D. (2016). Active Learning Through Discussion in E-Learning. International Journal of Active Learning, 1(1).